A new species of Pleroma (Melastomataceae) from high-altitude grasslands of the state of São Paulo, Brazil - Meyer, Fabrício Schmitz; Goldenberg, Renato (Phytotaxa, 2023)
A new species of Pleroma, endemic to the high-altitude grasslands of the state of São Paulo, is described. Pleroma curucutuense is morphologically similar to Pleroma caissara, but differs by the shrubby plants, 0.4–2 m tall (vs. arboreal plants, 2–7 m tall in P. caissara), smaller leaves, 2.4–5.6 × 1.2–2 cm (vs. 2.4–8.5 × 1.2–3.4 cm), with only 3 veins (vs. 5 veins), the smaller hypanthium, 5.5–6 × 4.5–5.5 mm (vs. 6.7–8.8 × 5.2–7.7 mm) and smaller sepals, 3.3–4.5 × 2.3–3.3 mm (vs. 6.7–10.2 × 2.7–4.6 mm). These species also occur in different habitats: P. curucutuense occurs above 750 m in high-altitude grasslands, while P. caissara occurs between 10–400 m elevation, in Restinga and Lowland and Submontane Atlantic Forest. According to our assessments based on IUCN criteria, P. curucutuense is preliminarily included in the Deficient Data category, because there is little information about its extent of occurrence and area of occupancy. Here we present its taxonomic description, comparisons with related species, illustrations made with photos of live and dehydrated specimens, and a distribution map. To facilitate its recognition, we present an identification key for the species of Pleroma that occur on high-altitude grasslands of the Parque Estadual da Serra do Mar, at the Núcleo Curucutu, where P. curucutuense has been collected.